BAWANG PUTIH, BAYAM DAN GARAM SEBAGAI ENERGI ALTERNATIF BATERAI - Mardwianta, Benedictus (SENATIK STT Adisutjipto, 2016)
The use of a battery to meet the electricity demand in Indonesia is still needed in the community. Inside there is a liquid electrolyte battery that serves as an energy source battery. In this study, the source of energy used is garlic, spinach and salt. All energy sources are mixed into three compositions based on a predetermined mass ratio. The purpose of this study was to determine the effect of the electrolyte of garlic, spinach and salt as an alternative source of electrical energy in the battery dry. How to adjust the composition of the material with a mass percentage used are: a. Composition I is 20% garlic, raw spinach 40% and 40% salt; b. Composition II was 40% garlic, raw spinach 20% and 40% salt; c. Composition III was  40% garlic, raw spinach 40% and 20% salt. Results from this research that a battery with a composition III has the highest electrical power to the composition III is 0974 mW. Therefore, a mixture of the composition III which contains garlic and spinach contain a lot of acid. To salt is not very influential on electric power because the salt is neutralKeywords: garlic, spinach and salt